Perancangan Algoritma Optimasi Pada Pengenalan Karakter Plat Nomor Kendaraan Menggunakan Pengolahan Citra (Komputika : Jurnal Sistem Komputer, 2020)
The introduction of vehicle number plates especially Indonesian number plates using image processing has not been widely used. Only from the government that utilizes the introduction of vehicle license plates with image processing as an automated electronic ticketing device installed on traffic signs. Some number plate recognition research was conducted to produce the best introduction. In this research, a method is used to optimize character recognition in recognition using image processing. This method analyzes the shape of the character similarity to the main character of the vehicle license plate number and analyzes where the character's position is. This method is able to increase the recognition of vehicle license plate characters using image processing with a percentage increase in accuracy from 80% to 94%.